Association between health literacy and sugar-sweetened beverages consumption among Filipinos - Aguilar, Michelle Ann D.; Tolabing, Ma. Carmen C.; Saniel, Ofelia P.; Sumalapao, Derick Erl P.; Tempongko, Ma. Sandra B.; Talavera, Maria Theresa M. (Manila College of Public Health, University of the Philippines Manila, 2024)
Background: Sugar-sweetened beverages (SSBs) are a common part of Filipino meals. Increase SSB consumption is linked to weight gain and increased risk of noncommunicable diseases (NCDs). Previous studies have shown that health literacy (HL) is associated with positive health outcomes. However, there are limited studies examining its relationship with specific dietary behavior, including SSB consumption.

Objective: The primary objective of this study is to determine if HL is associated with SSB consumption among Filipinos (15 to 70 years old).

Methods: An analytic cross-sectional study using secondary data from the 2018-2019 National Health Literacy Survey (NHLS) was conducted. A total of 1,765 study participants (15 to 70 years old) were included. Socio-demographic information, daily SSB consumption, and HL level (limited or sufficient) were extracted. Multivariate logistic regression was conducted to estimate adjusted odds ratios and confidence intervals for daily SSB consumption.

Findings: Out of the 1,765 study participants, 64.14% reported consuming (≥1 SSB drink per day, of whom majority (57.52%) were adults (31 to 59 years old), females (72.21%), married or in common-law partnership (65.70%), living in the Luzon region (47.23%), urban residents (71.94%), high school graduates (30.52%), have an annual household income of Php 100,000-249,999 (37.03%), and employed (92.61%). Age, sex, and subnational levels were found to be significantly associated with the consumption of ≥1 SSB drink(s) per day. A weak association was found between HL and SSB consumption (aOR: 0.9591; 95% CI: 0.7832, 1.1747), that is, the adjusted odds of having limited HL were found to be slightly lower among those consuming ≥1 SSB drink(s) per day than those who consume <1 SSB drink/day. However, this association was found to be not statistically significant.

Conclusion: There was a high prevalence of daily SSB consumption among Filipinos. Among the variables considered, only age, sex, and subnational level were found to be significant determinants of SSB consumption. This research fills a gap in the literature regarding the role of HL in specific dietary behaviors, specifically SSB consumption within the Philippine context. The findings of the study may provide valuable insights for targeted health promotion and education interventions in reducing SSB consumption among Filipinos.
Includes references and appendices.
Thesis
Keywords: Health literacy -- Philippines; Sugar-sweetened beverages -- Health aspects -- Philippines; Nutrition and health -- Philippines